Ganoderma lucidum-derived polysaccharide enhances coix oil-based microemulsion on stability and lung cancer-targeted therapy - Guo, Jian (Drug Deliv, 2018)
The aim of this study is to explore the influence of Ganoderma lucidum-derived polysaccharides (GLP) to coix oil-based microemulsion on pharmaceutical performance and anti-lung cancer treatment. GLP-integrated coix oil-based microemulsion (MEs(PS-GLP)) exhibited a clear spherical shape, small particle size, and good hydrodynamics similar to the coix oil-based microemulsion, but showed a lower zeta potential and a better stability. Fluorescence resonance energy transfer analysis presented that GLP was integrated with microemulsion as a single system. Notably, the average molecular distance between polysaccharide and microemulsion was approximately 1.7 nm. The half-maximal inhibitory concentration of MEs(PS-GLP) against A549 cells was about 119 μg/mL. In vivo imaging studies showed that introduction of GLP promoted the tumor-specific accumulation of microemulsion in comparison with controls. In vivo, antitumor results showed that MEs(PS-GLP) markedly inhibited the tumor growth of A549-bearing xenograft nude mice and obviously improve the serum immune index. Collectively, this study demonstrates the potential mechanism of spatial relation between polysaccharides and microemulsion and validates the significances of GLP on tumoral accumulation and antitumor efficacy.